Phenotypic and genetic characterization of resistance in Arabidopsis thaliana to the oomycete pathogen Phytophthora parasitica - Meng, Yuling; Huang, Yihua; Wang, Qinhu; Wen, Qujiang; Jia, Jinbu; Zhang, Qiang; Huang, Guiyan; Quan, Junli; Shan, Weixing (Frontiers in Plant Science, 2015)
The interaction between Arabidopsis thaliana and the oomycete pathogen Phytophthora parasitica emerges as a model for exploring the molecular basis and evolution of recognition and host defense. Phenotypic variation and genetic analysis is essential to dissect the underlying mechanisms in plant–oomycete interaction. In this study, the reaction phenotypes of 28 A. thaliana accessions to P. parasitica strain Pp016 were examined using detached leaf infection assay. The results showed the presence of four distinct groups based on host response and disease development. Of all the accessions examined, Zurich (Zu-1) is highly resistant to P. parasitica. Microscopic characterization showed that rapid and severe hypersensitive response at the primary infection epidermal cells is associated with disease resistance. Furthermore, Zu-1 is resistant to a set of 20 diverse P. parasitica strains, which were collected from different host plants and exhibited differential specificities on a set of tobacco cultivars. However, Zu-1 is susceptible to P. parasitica when the root is inoculated, suggesting differential expression of associated resistance genes in the root and foliar tissues. Genetic analysis by crossing Zu-1 and the susceptible accession Landsberg (Ler) showed that the resistance in Zu-1 to P. parasitica is semi-dominant, as shown by infection assays of F1 progenies, and is likely conferred by a single locus, defined as RPPA1Zu-1 (for Resistance to P. parasitica 1), as shown by analysis of F2 segregating populations. By employing specific-locus amplified fragment sequencing (SLAF-seq) strategy to identify molecular markers potentially linked to the locus, the strongest associated region was determined to be located between 7.1 and 11.2 Mb in chromosome IV. The future cloning of RPPA1Zu-1 locus will facilitate improved understanding of plant broad-spectrum disease resistance to oomycete pathogens.